Cervicofacial actinomycosis - report of two cases - Bochev, Valo (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2003)
Human actinomycosis is a bacterial infection caused primarily by Actinomyces israelii, a resident of the oral cavity. The cervicofacial region is most commonly affected; thoracic and abdominal forms of the disease have also been distinguished. Actinomycosis is sometimes difficult to diagnose and it should be borne in mind in the differential diagnosis of numerous infectious and non-infectious diseases. We describe two patients with cervicofacial actinomycosis which on initial examination were diagnosed as "submandibular phlegmona".
Keywords: Actinomyces; Actinomycosis, Cervicofacial; Adult; aktinomikoza; Aktinomikoza cervikofacialna; bakterijske infekcije; Diagnosis; diagnostika; Odrasli; Pathology